U.S. Unconventional Monetary Policy and Risk Tolerance in Major Currency Markets - Athanasios Fassas; Dimitris Kenourgios; Stephanos Fassas (The European Journal of Finance, 2021)
This paper studies the effects of U.S. unconventional monetary policy announcements on the implied volatility of three major currency pairs, Dollar/Euro, Dollar/British Pound and Dollar/Yen by using panel data analysis along with several model specifications and robustness tests. Monetary policy announcements not only have an effect on the realized behavior of asset prices, but also influence market participants’ expectations regarding future volatility. Our empirical findings show that Federal Reserve’s unconventional monetary policy announcements significantly reduce the market expectations about future realized volatility of exchange rates, suggesting that lax monetary policy leads to elevated risk-tolerance in currency markets. Furthermore, our findings indicate that market participants’ expectations respond differently to the different rounds of U.S. quantitative easing.